2001
DOI: 10.1002/yea.748.abs
|View full text |Cite
|
Sign up to set email alerts
|

Extensive chromosome translocation in a clinical isolate showing the distinctive carbohydrate assimilation profile from a candidiasis patient

Abstract: Variation of the electrophoretic karyotype is common among clinical strains of Candida albicans and chromosome translocation is considered one of the causes of karyotypic variation. Such chromosome translocations may be a mechanism to confer phenotypic diversity on the imperfect fungus C. albicans. A clinical strain, TCH23, from a vaginal candidiasis patient shows distinct carbohydrate assimilation profile, serotype B, no chlamydospore formation and an atypical karyotype (Asakura et al., 1991). To examine the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2002
2002
2010
2010

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(10 citation statements)
references
References 25 publications
(55 reference statements)
0
10
0
Order By: Relevance
“…To investigate the possibility of chromosome translocation in transformants containing extra chromosome DNA bands, we selected 19 DNA probes that are located at or near at one end of each chromosome in strain 1006 (Table 2). We reported previously that these probes helped us to identify chromosome translocation products (Iwaguchi et al, 2001). Probes from chromosomes R, 1, 5 and 7 hybridized to extrachromosomal DNA bands in five of the transformants.…”
Section: Chromosome Translocations Induced By the Insertion Of Rubmentioning
confidence: 92%
See 3 more Smart Citations
“…To investigate the possibility of chromosome translocation in transformants containing extra chromosome DNA bands, we selected 19 DNA probes that are located at or near at one end of each chromosome in strain 1006 (Table 2). We reported previously that these probes helped us to identify chromosome translocation products (Iwaguchi et al, 2001). Probes from chromosomes R, 1, 5 and 7 hybridized to extrachromosomal DNA bands in five of the transformants.…”
Section: Chromosome Translocations Induced By the Insertion Of Rubmentioning
confidence: 92%
“…Five transformants (tRB6, tRB16, tRB26, tRB29 and tRB41) contained extra chromosome DNA bands. Extrachromosomal DNA bands are usually considered to be the products of chromosome translocation (Chu et al, 1993;Navarro-Garcia et al, 1995;Iwaguchi et al, 2000Iwaguchi et al, , 2001. In the case of the RUS blaster, we obtained 36 transformants and the insertion events occurred on all of the chromosomes except for 3 and 4.…”
Section: Integrative Transformation Of the Ura3 Blaster Into The Mrs mentioning
confidence: 99%
See 2 more Smart Citations
“…These karyotypes were rather similar to those of C. stellatoidea type I but the authors discarded the hypothesis that their seven isolates belonged to the latter species on the basis of positive assimilation of sucrose. 30 Ten years later, Iwanughi et al [76] analysed the chromosome structure of the TCH23 strain (one of the seven atypical strains isolated by Asakura et al [30]) and found that seven chromosomal DNA bands in this strain were reciprocal chromosome translocations. Therefore, it is possible that the inability to assimilate some carbon sources and to produce chlamydospore by C. africana is due to these genetic rearrangements that occurred within its genome.…”
Section: Genotypic Characteristics and Molecular Identificationmentioning
confidence: 99%